Evaluation of phase-frequency instability when processing complex radar signals - Juliy Boiko; Lesya Karpova; Oleksander Eromenko; Yevhen Havrylko (Institute of Advanced Engineering and Science, 2020)
A new radar system for digital signal processing before detection is proposed. These are the guidelines for selecting an intermediate frequency for signal processing. The features of signal processing in the case of echo-signal selection by the features of the correlation properties of their complex bypass are described. This paper presents the study of ambiguity function (AF) when processing complex radar signals. In this work, the AF synthesis was performed considering non-determined components and the presence of phase-frequency instability. The received result enhances the potentials for distinguishing an incoherent radar signal. The numerical simulation results of received AF are presented. Considering fluctuation components in the complex AF, depending on the laws of the distribution of amplitude and frequency fluctuations and their parameters, allowed to get the gain in the width of the main lobe from the units to tens of times. Paper represents original analytical expressions for AF of radio-signals modulated by narrow band random processes with various distribution laws.